Relationship Between Parenting Styles And Subjective Well-Being Of Undergraduate Youths In The University Of Port Harcourt - Manuel, Amininiye Macgregor; Asuquo, Ntiedo (Advances in Social Sciences Research Journal, 2021)
This study investigated the relationship between parenting styles and subjective well-being among undergraduate youths in the University of Port Harcourt using the correlational research design. The study was guided by five research questions and their corresponding null hypotheses. The sample for the study was composed of 400 undergraduate students drawn using the purposive sampling technique. Two instruments were used for data collection which were the parenting style inventory and the subjective well-being inventory. The instruments were assessed for reliability and validity and were shown to be suitable. Data analysis was done using linear regression and multiple regression for answering the research questions, while ANOVA associated with linear and multiple regression were used to test the null hypotheses. Result showed that authoritative parenting style had the highest independent prediction on the subjective well- being of youths, while authoritarian had the least independent prediction. On the basis of the result obtained, it was recommended that parents adopt the authoritative parenting style when dealing with their children so as to achieve an optimal state of subjective well-being.